A Statistical Process Development Model in Thesis Writing for Graduate Students at Mahidol University in Thailand - Youthao S. (2023)
The graduate thesis is a fundamental part of creating educational expertise. This study aims to expand the use of the statistical technique in graduate theses. The data collection consists of quantitative and qualitative data from advisers and graduate college students at Mahidol University. The sample includes 650 university students and fifteen key informants, including nine students and six supervisors, divided into three groups; health science, science and technology, and social sciences and the humanities. The results of the study showed that most of the students who collected data worked on a thesis with quantitative research (50.42%), followed by mixed methods research (38.40%) and qualitative research (10.52%). Problems arise when graduate college students lack comprehension and are unable to select the most accurate data for their thesis. This study presents findings regarding the guidelines for the use of statistical techniques to analyze data from theses or dissertations, teaching and learning strategies or additional training in the selection and use of statistics, guidelines for the selection and use of statistics in data analysis, and the use of e-learning to teach statistics.